Levantamento das espécies de formigas e seu potencial no controle da broca do cafeeiro em diferentes sistemas de cultivo de café - Simonetti, Janet Alfonso (2022)
The coffee borer, Hypothenemus hampei, is native to Central Africa, where its main host is robusta coffee (Coffea canephora). From an economic point of view, the borer is considered one of the most important pests of coffee cultivation, due to the direct damage caused to the fruit, the high population density, the difficulties in achieving an efficient control and the limitations to the commercialization of the affected grains. Currently, the drill continues to cause significant economic losses in the world. In Brazil alone, this insect causes estimated losses of US$ 215-358 million per year. In coffee agroecosystems, ants respond to different practices, involving plant diversification of each habitat and management intensity. Predator ants, as well as other natural enemies that act in biological control in these systems, have been studied in relation to the beetle H. hampei. For these reasons, the general objective of this work was to evaluate ant populations in order to regulate H. hampei populations in different coffee growing systems in Brazil. The study was carried out in 12 properties, four areas of conventional coffee in full sun, four organic in full sun and four organic in shade, belonging to producers associated with the Cooperativa de Produtores Familiares de Poço Fundo e Region (COOPFAM). Sampling was carried out during the coffee harvest period (May 2019) and the beginning of the off-season (September 2019), using pitfall traps, attractive baits and fruit collection from the plant and the ground. The collected ants were identified to the lowest possible taxonomic level. In total, 65 species of ants belonging to 32 genera and seven subfamilies were collected, with 46 species recorded in pitfall traps and 30 in attractive baits. For the fruits collected from the plant and on the ground, 22 species were identified, distributed in 11 genera and four subfamilies. The subfamily with the highest number of taxa was Myrmicinae, followed by Formicinae and Ponerinae. The results showed that the different coffee cultivation systems, organic and conventional, whether shaded or in full sun, showed no difference in terms of ant species richness, but rather in terms of species composition, a parameter to be considered in the comparison between systems of cultivation studied. In the three coffee growing systems, the borer infestation percentage reached the level of economic damage. The highest infestation rates were found in the conventional system in full sun (CSL), with an average of 8.9 % in the fruits of the plant and 11.1 % in the fruits of the ground, followed by the shaded organic system (OSM), with 8 .4 % on the plant and 7.9 % on the ground and, finally, the one with the lowest infestation rate, the organic system in full sun (OSL), with 5.8 % on the plant and 6.3 % on the ground. When compared with the composition of the ants, there is a close relationship between the system with the lowest rate of infestation by the borer and those with greater richness and frequency of ants. Obtaining this information provides a basis for recommendations for biological control in coffee growing in the south of Minas Gerais.